Sensitization of the sphenopalatine ganglion (SPG) by periodontal inflammation: A possible etiology of sinusitis and headache in children - Haryono Utomo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Sinusitis is a frequent complication of allergic rhinitis. Theoretically, sinusitis could be found in human since infancy. The prevalence of diagnosed sinusitis is 20% of ambulatory patients in daily practice. Unfortunately, a lot of sinusitis cases must be treated by surgical operation. Other cases are treated conservatively with decongestants, corticosteroids, antibiotics and diathermy. However, dental treatment approach for sinusitis management is rarely discussed. Headache, especially migraine is also a common problem in children. Sinusitis and migraine, are closely related; sinusitis sufferers often accompanied by migraine and vice versa. This phenomenon resulting in misdiagnosis of the main etiology of sinusitis and migraine; if this case happens in young children, the diagnosis should be more complicated. Dental procedures which may directly reduce the periodontal inflammation were done to children diagnosed as sinusitis by otolaryngologist and pediatrician. In a short period of time, the sinusitis and headache symptoms subsided. The objective of this case reports is to propose the possible explanation of the neurogenic switching mechanism cut off, that resulting in the instant relief of sinusitis and headache symptoms. Regarding the immediate relief of the symptoms, the role of autonomic nervous system should also be considered. Since parasympathetic innervations of nasal, sinus mucosa and maxillary periodontal tissues originated from the sphenopalatine ganglion; the conclusion is that the periodontal inflammation may sensitize the sphenopalatine ganglion which may trigger sinusitis and headache in children.